Transformation of State Civil Apparatus Learning Task Administration Services through the J-SiLAKON Application - Fu’adah, Washiqotul; Hidayat, Rofiq (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
The emergence of the Covid-19 pandemic and the progress of industry 4.0. The developments encourage the government to digitize public administration services. The Jember Regency Personnel and Human Resources Development Agency (BKSDM) therefore launched a web-based application named J-SiLAKON (Jember Online Personnel Services System) for study assignments to increase effectiveness and efficiency in providing services, and to encourage good governance. This research examines the effectiveness of the transformation of ASN learning task administration services through J-SiLAKON at the Jember Regency Education Office. By Using a qualitative case study approach, data were collected through semi-structured interviews, passive observation, and primary documentation involving J-SiLAKON operators and staff from the Teachers and Education Personnel Division. The analysis of data involved condensation, presentation, and conclusion drawing, with triangulation to ensure data validity. Results showed that J-SiLAKON is easy to learn, control, understand, and use, thus improving users' proficiency in performing their duties. It provided significant benefits, including faster work, improved employee performance, increased productivity, and more effective administrative services. Overall, the J-SiLAKON application improves the efficiency, productivity and transparency of ASN study assignment administration services at the Education Office, meeting user expectations and improving the performance of the Education office.